Effect Of Season On Hatching Performance Of Giriraja Variety Of Chicken - Jayachitra , S. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The present study was taken up with the objectives of analyzing the various hatchability parameters with respect to season in Giriraja birds. A total of 962 birds were used to record the hatchability performance at different seasons in district livestock farm, Orathanadu. The total egg hatchability and fertile egg hatchability were recorded highest in March and April months but it was lower in October to December and lowest in May, June months. The early embryonic mortality, late embryonic mortality and dead in shell percentage were highest in summer months due to high environmental temperature. The study revealed that the birds performed better in egg production and hatchability in March and April months.
Keywords: Giriraja; Season; Hatchability